Burden of active tuberculosis among patients with diabetes mellitus in Sub-Saharan Africa: A systematic review and meta-analysis - Gizachew Ambaw Kassie; Getachew Asmare Adella; Beshada Zerfu Woldegeorgis; Afework Alemu; Amanuel Yosef Gebrekidan; Kirubel Eshetu Haile; Amelework Gonfa Efa; Gedion Asnake Azeze; Yordanos Sisay Asgedom (Heliyon, 2024)
Background: The simultaneous occurrence of diabetes mellitus and tuberculosis presents a significant health challenge, complicating diagnosis, treatment, and outcomes. Despite this, tuberculosis screening is not routinely conducted for diabetes patients, and limited information exists regarding tuberculosis prevalence among diabetics in Africa. Thus, this study aimed to determine the pooled prevalence of tuberculosis among diabetes mellitus patients in Sub-Saharan Africa. Methods: A systematic search was conducted in PubMed, Medline, Google Scholar, and African Journal online library databases to identify studies reporting tuberculosis burden among diabetes patients in Sub-Saharan Africa. Data extraction was performed using an Excel spreadsheet, with analysis carried out in Stata version 14. The pooled prevalence was estimated using a Der-Simonian-Laird random-effects model. Heterogeneity among studies was assessed using I-squared test statistics, and subgroup analyses were conducted to identify heterogeneity sources. Risk of bias assessment and sensitivity analysis were also performed. Results: The systematic review and meta-analysis included twelve studies with 13,002 participants. The combined prevalence of tuberculosis among diabetes patients in Sub-Saharan Africa was 4.11 % (95 % confidence interval: 2.97–5.25); I2 = 89.4 %). Subgroup analysis revealed a pooled tuberculosis prevalence of 4.6 % among diabetes patients in East Africa and 2.36 % in Southwestern African countries. Conclusions: This research indicates an elevated prevalence of tuberculosis among diabetes patients in sub-Saharan Africa. The findings highlight the urgent need for tuberculosis screening in diabetes patients and the implementation of effective prevention strategies to address the dual burden of comorbid tuberculosis and diabetes mellitus.